Idikator Kinerja Pendidikan Akupunktur Pada Prodi D-III Akupunktur Jurusan Akupunktur Politeknik Kesehatan Kemenkes Surakarta - Joko Tri Haryanto; Purwanto Purwanto; Jatmiko Rinto Wahyudi (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Curriculum, Teaching, and Learning (PBM), Educator and Education Personnel, Academic Culture, Prodi D-III Acupuncture. Professional health workers produced by the Health Education institutions qualified personnel. Quality of learning experience can be good when it managed to change attitudes, behaviors, and skills of students in accordance with the purpose of education. Weakness in improving the quality of education in Indonesia for this is that these programs apart is done partially and not comply with the quality system is easily understood by all program managers in education. Methods This study used a qualitative approach to the type of case studies. Informants are citizens and academics Prodi D-III Acupuncture Acupuncture Department of Health Polytechnic Surakarta which is determined by the proportion of samples. Data were collected through orientation, observation, interviews, and documentation. Interactive data analysis and data validity based on triangulation from various data sources. The results of this study found that aspects of the curriculum have been adapted to the progress of science and technology, and merupakan competency-based curriculum and national standards on Health Manpower Education.